Cover Picture: Kinetic and Thermodynamic Study of the Reduction of 1, 1‐Diphenylethylene by a Thermally Frustrated Diethyl Ether‐BCF Lewis Pair (Isr. J. Chem. 2/2015). Issue 2 (February 2015) - Whittemore, Sean M.; Autrey, Tom
<x xml:space="preserve">Abstract</x> The cover picture shows the time dependent heat release for the catalytic reduction of diphenylethylene by the frustrated Lewis pair (FLP) composed of diethyl ether and tris(pentafluorophenyl borane), first reported by Hounjet and co‐workers (Angew. Chem. Int. Ed. 2013, 52, 7492). The modified Calvet calorimeter vessels described by Karkamkar et al. (Dalton Trans. 2013, 42, 615) provide an experimental approach to simultaneous measure of enthalpic driving force and rate of reduction in FLP catalysis. Read more on page 196, and in the articles on FLP chemistry in this special issue. The authors gratefully acknowledge Dr. Jonathan M. Darmon (PNNL) for designing the cover picture.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>